O insider trading no direito brasileiro - Müssnich, Francisco Antunes Maciel (2015)
The potential damage caused by insider trading is very high, because the offense affects not only the parties directly related to the transaction carried out while in possession of inside information, but also the stock market as a whole, undermining investor confidence. Severe sanctions under the administrative, civil and criminal law are necessary to discourage the offense. In this, Brazil’s securities regulator, the CVM - Comissão de Valores Mobiliários, plays a particularly important role because it wields the state’s power to intervene in the capital markets. At the same time, liability for insider trading offense should be based on a strong body of evidence, even if the evidence of insider trading is indirect only. The use of information barriers, which reduces the potential for conflicts of interest by restricting access to undisclosed material information, is not in itself sufficient to exclude liability for insider trading. Theories such as the 'corporate mind' can make Chinese walls ineffective protection against liability, even if they properly perform their function of segregating information. The theory of constructive or imputed knowledge cannot be applied in determining liability for insider trading